Cat scratch‐induced Pasteurella multocida necrotizing cellulitis in a dog. Issue 4 (5th June 2013) - Banovic, Frane; Linder, Keith; Boone, Alison; Jennings, Sam; Murphy, K. Marcia
Abstract : Background: In humans, rapidly developing Pasteurella multocida cellulitis after a cat scratch or bite is a well‐known entity that sometimes progresses to necrotizing fasciitis and can be fatal. Case report: A 3‐year‐old female spayed whippet dog developed ecchymosis, swelling and pain within 24 h of being scratched by a cat on the ventral thorax. Over the following days, while being treated only with pain medications, the lesions rapidly progressed into haemorrhagic bullae with expanding skin necrosis. A heavy growth of P. multocida was seen on bacterial cultures, and histological examination showed marked, suppurative panniculitis with necrosis of the epidermis, dermis and panniculus. Special histological stains highlighted a moderate amount of Gram‐negative coccobacilli admixed with inflammatory cells. Complete resolution was achieved with surgical debridement, skin grafting and intravenous antibiotic treatment. Positive bacterial culture for P. multocida, in conjunction with the history, clinical findings, histology results and the rapid response to therapy, strongly supports a diagnosis of P. multocida necrotizing cellulitis. Conclusions and clinical importance: Complications of cat bite‐associated P. multocida infections in humans are well known. To the authors' knowledge, this is the first documentation of P. multocida necrotizing cellulitis in a dog following a cat scratch wound. This case highlights the rapidity and severity of P. multocida cellulitis, if not recognized and treated early. Veterinarians should include P. multocida in the differential diagnosis of any local wound infection following a cat scratch.